2018
DOI: 10.1155/2018/8025062
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miRNAs in Serum Exosomes versus Hippocampus in Methamphetamine‐Induced Rats and Intervention of Rhynchophylline

Abstract: Objective To compare the expressions of miRNAs (microRNAs) in serum exosomes and in hippocampus and to provide insights into the miRNA-mediated relationship between peripheral and central nervous systems in the presence of methamphetamine. Methods Published results on conditioned place preference (CPP) in rats conditioned by methamphetamine were replicated. The expressions of miRNAs in serum exosomes and hippocampus were determined by gene-chip sequencing. We then predicted the potential target genes of select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Rodent models have also been used to investigate the effects of MA on miRNA expression in brain and serum EVs (Bosch et al., 2015; Du et al., 2016; Li et al., 2018; Li et al., 2018; Sim et al., 2017; Zhu et al., 2015,). In the rat VTA, miRNAs previously associated with MA addiction (miR‐124 and miR‐181a) as well as novel miRNAs (miR‐125a‐5p and miR‐145) are decreased in expression following 14 days of abstinence (Bosch et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Rodent models have also been used to investigate the effects of MA on miRNA expression in brain and serum EVs (Bosch et al., 2015; Du et al., 2016; Li et al., 2018; Li et al., 2018; Sim et al., 2017; Zhu et al., 2015,). In the rat VTA, miRNAs previously associated with MA addiction (miR‐124 and miR‐181a) as well as novel miRNAs (miR‐125a‐5p and miR‐145) are decreased in expression following 14 days of abstinence (Bosch et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes act as carriers to follicles from the surrounding somatic cells as well as the body and blood to influence oocyte maturation. Moreover, immune stimulus has been shown to enhance vasodilatation to promote exosomal function [ 29 , 30 ]. Past work has also shown that miR-194a family expression plays an important role in immunological responses and function, including the flounder [ 31 ] and zebrafish [ 32 ] immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…2. Exosomes is carriers to follicles from surrounding somatic cells body blood to influence oocyte maturation, which immune stimulus could enhance vasodilatation in order to promote EXs function 29,30 . It is also indicated that miR-194a family expression play important roles in immunology response and function, such as flounder immune response 31 and zebrafish 32 .…”
Section: Discussionmentioning
confidence: 99%